2013
DOI: 10.2319/091312-730.1
|View full text |Cite
|
Sign up to set email alerts
|

Camouflage treatment of skeletal Class III malocclusion with multiloop edgewise arch wire and modified Class III elastics by maxillary mini-implant anchorage

Abstract: Objective: To evaluate the effect of the multiloop edgewise arch wire (MEAW) technique with maxillary mini-implants in the camouflage treatment of skeletal Class III malocclusion. Materials and Methods: Twenty patients were treated with the MEAW technique and modified Class III elastics from the maxillary mini-implants. Twenty-four patients were treated with MEAW and long Class III elastics from the upper second molars as control. Lateral cephalometric radiographs were obtained and analyzed before and after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 14 publications
(21 reference statements)
1
38
1
6
Order By: Relevance
“…9 To avoid this, several studies have reported mini-implant-assisted distalization of the lower dentition. [8][9][10][11][12] The advantage of this method is its ability to tip the lower molars distally with intrusion and the lower incisors lingually with extrusion, while avoiding any movement of the upper dentition. [8][9][10][11][12] Miniimplants can be installed in the posterior area of the maxilla or the mandible, with a goal to cancel or avoid the vertical force vector of the Class III elastics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 To avoid this, several studies have reported mini-implant-assisted distalization of the lower dentition. [8][9][10][11][12] The advantage of this method is its ability to tip the lower molars distally with intrusion and the lower incisors lingually with extrusion, while avoiding any movement of the upper dentition. [8][9][10][11][12] Miniimplants can be installed in the posterior area of the maxilla or the mandible, with a goal to cancel or avoid the vertical force vector of the Class III elastics.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Class III elastics result in mesial movement of the upper dentition and distal movement of the lower dentition with proclination of upper and retroclination of the lower dentition. 2,[5][6][7][8] They also induce extrusion of the upper molars and lower incisors, resulting in counterclockwise rotation of the occlusal plane and an increase in the facial height. 5,8 However, proclined upper incisors and flat smile arcs are unfavorable esthetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu durum fasiyal profilin statik ve dinamik güzelliğini fazlasıyla bozmakta ve aynı zamanda tedavinin stabilitesini de riske atmaktadır. 13,14 Sınıf III malokluzyonun kamuflaj tedavisinde son yıllarda oldukça popüler olan iskeletsel ankraj mekaniklerinin kullanımı ile mandibular dentistyonun en-masse distalizasyonu maksiller keserlerin aşırı proklinasyonunu engellemek açısından oldukça etkili olmaktadır. 12,14 Bu vaka raporunun amacı, iskeletsel Sınıf III malokluzyona sahip büyüme ve gelişimi tamamlanmış olan bir hastanın iskeletsel ankraj kullanılarak yapılan kamuflaj tedavisinin sonuçlarını sunmaktır.…”
Section: Introductionunclassified